3x-5x(x-5)=-8+4x-9

Simple and best practice solution for 3x-5x(x-5)=-8+4x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5x(x-5)=-8+4x-9 equation:



3x-5x(x-5)=-8+4x-9
We move all terms to the left:
3x-5x(x-5)-(-8+4x-9)=0
We add all the numbers together, and all the variables
3x-5x(x-5)-(4x-17)=0
We multiply parentheses
-5x^2+3x+25x-(4x-17)=0
We get rid of parentheses
-5x^2+3x+25x-4x+17=0
We add all the numbers together, and all the variables
-5x^2+24x+17=0
a = -5; b = 24; c = +17;
Δ = b2-4ac
Δ = 242-4·(-5)·17
Δ = 916
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{916}=\sqrt{4*229}=\sqrt{4}*\sqrt{229}=2\sqrt{229}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(24)-2\sqrt{229}}{2*-5}=\frac{-24-2\sqrt{229}}{-10} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(24)+2\sqrt{229}}{2*-5}=\frac{-24+2\sqrt{229}}{-10} $

See similar equations:

| 6/x=1.429 | | 4y+8=5y-3 | | 5y-3=4y+8 | | 5y-3=4y+9 | | 2x-20=48+(x+10) | | 15x-6x=810 | | 0=17(15+15x) | | 5(7f-3)=22(f-1) | | 9(2b+7)=11(b+14) | | -3(4p-5)=-7(-5-2p) | | -3(4p-5)=-7(-5-2) | | 7a-5=5a+9 | | x/6+5/3=8/6-x/6 | | 5a-2=4a+7 | | 27+13x=-18+8x-4x | | (x-3)/2=x | | 4x+60=x+70-3x | | -5x-50=-10x+60 | | 4x+40=6x=10 | | -44+x=3x+40 | | -7x+45=2x+9 | | 4w-20=4w-20 | | 11x+47=-5x-49 | | 14x+3x+2=53 | | 9x+48=3x+96 | | 7x-27=-7x+15 | | x2+8x−84=0 | | 7x-27=7x+15 | | 5a-8=7a+12 | | -6|v|=0 | | 5^c=625 | | 4-(x+3)/2=-x-1 |

Equations solver categories